Efektivitas Penggunaan Dana Bagi Hasil Cukai Hasil Tembakau (DBH-CHT) Sebagai Instrumen Pemulihan Kesehatan Di Kota Kediri - Cania Prameswari Hadi Waluyo; Lego Karjoko; Rahayu Subekti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study to determine the use of revenue sharing funds of tobacco products excise as a health restoration instrument in Kediri City in 2023 and the effectiveness of Minister of Finance Regulation Number 215/PMK.07/2021 related to the use of revenue sharing funds of tobacco products excise as a health restoration instrument in Kediri City. Qualitative empirical legal research constitutes this study. Data sources and types consist of primary and secondary information. Interviews with representatives of the Kediri City Health Office and the Kediri City Regional Secretariat were utilised to acquire the data. The findings of this study indicate that the health recovery efforts in Kediri City have been largely ineffective due to inadequate implementation of the budget plan. In addition to the aforementioned, the efficacy of Minister of Finance Regulation Number 215/PMK.07/2021 is hindered by a number of obstacles pertaining to law enforcement, facilities, the community, and culture.